The DevSecOps and Agency Theory - Lee, Jong Seok (2018 IEEE International Symposium on Software Reliability Engineering Workshops (ISSREW), 2018)
An effective implementation of DevSecOps requires an increased focus on collaborations between different work groups or disciplines within IT (development, security, and operations/implementation). Nonetheless, different groups are still too often reluctant to trust each other, or inter-group conflicts tend to commonly occur. Against this backdrop, in this research I develop a framework based on Agency Theory that sheds light on the role of goal incongruency and information asymmetry in the DevSecOps context.